Estimation of Biochemical Oxygen Demand Based on Dissolved Organic Carbon, UV Absorption, and Fluorescence Measurements - Jihyun Kwak; Bumju Khang; Eunhee Kim; Hyunook Kim (Journal of Chemistry)
Determination of 5-d biochemical oxygen demand (BOD5) is the most commonly practiced test to assess the water quality of surface waters and the waste loading. However, BOD5 is not a good parameter for the control of water or wastewater treatment processes because of its long test period. It is very difficult to produce consistent and reliable BOD5 results without using careful laboratory quality control practices. This study was performed to develop software sensors to predict the BOD5 of river water and wastewater. The software sensors were based on the multiple regression analysis using the dissolved organic carbon (DOC) concentration, UV light absorbance at 254 nm, and synchronous fluorescence spectra. River water samples and wastewater treatment plant (WWTP) effluents were collected at 1-hour interval to evaluate the feasibility of the software sensors. In short, the software sensors developed in this study could well predict the BOD5 of river water (r=0.78) and for the WWTP effluent (r=0.90).